Virtual Primary Care—Improving Access, Efficiency, and Patient Experience - Crystal Kong-Wong; Michelle Lin; John D. Scott (Telemedicine Reports)
The United States faces a growing scarcity of primary care resources within an already overstressed and poorly accessible health care system. Many health care organizations are evaluating novel models of care and adoption of digital technologies to improve primary care access and efficiency of health care delivery. This article describes a virtual primary care (VPC) model that expands access and increases the efficiency of the traditional primary care team by utilizing on-demand and asynchronous digital tools. In the first year of operations, this service line provided >21,000 on-demand telemedicine visits and >4,000 asynchronous eVisits. The VPC service line improved access to primary care services in a financially successful and sustainable model.